2016
DOI: 10.2298/gensr1601423a
|View full text |Cite
|
Sign up to set email alerts
|

Transformation, evaluation of GTGene and multivariate genetic analysis for morpho-physiological and yield attributing traits in Zea mays

Abstract: Maize is the 3rd major crop grown all over the world that fulfills the needs of millions of people. Various biotic and abiotic factors caused reduction in grain yield of maize, among them weeds show most adverse effects. Objective of this study was to develop glyphosate resistance maize for developing maize hybrids and synthetic varieties with high grain and fodder yield potential. Glyphosate is a broad spectrum herbicide and resistance of crop against the herbicide, allows post emergence app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Multivariate techniques to select traits related to S. frugiperda tolerance in popcorn genotypes were also used by [7, 17] and as in this study, the application of multivariate analysis allowed a significant reduction in the number of traits. This raises the chances of a more effective selection, since the smaller number of traits prevents the effect of interrelationships among them, avoiding redundancy and mistakes in the process of selecting promising genotypes [8].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Multivariate techniques to select traits related to S. frugiperda tolerance in popcorn genotypes were also used by [7, 17] and as in this study, the application of multivariate analysis allowed a significant reduction in the number of traits. This raises the chances of a more effective selection, since the smaller number of traits prevents the effect of interrelationships among them, avoiding redundancy and mistakes in the process of selecting promising genotypes [8].…”
Section: Resultsmentioning
confidence: 99%
“…Resistance is the set of physical, chemical and morphological traits that will negatively affect the insect's oviposition and feeding behavior, while tolerance is the set of traits that will cause plants to withstand the attack of insects without substantial reductions in productivity in comparison with other susceptible genotypes [8,9,11]. In this study, the hypothesis was proposed that tolerance to S. frugiperda can be found in popcorn germplasm from tropical regions and that multivariate analysis can discriminate the main traits related to the identification of tolerance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From 1000 resistant multiplied plants (CPF-246), 15 plants were positive for CEMB- Cry 1Ac, CEMB- Cry 2A and CEMB-GTGene, resulting transformation efficiency 1.5% after optimized glyphosate spray assay (1200 mL/80 L/acre). In monocots, the transformation efficiency was reported from 1 to 5% 30 while co-integration of combine two genes was 85% when a combination of 14 diverse (pUC- based) plasmids was transformed 74 . Joyce et al 52 reported 0.8–4.8% transformation efficiency in sugarcane.…”
Section: Discussionmentioning
confidence: 99%